Effects of age at marriage on pregnancy outcome and nutritional status of mother and child in Bogor West Java, Indonesia - Kusharto, Clara Meliyanti 1951-; Florencio, Cecilia A. (Quezon City College of Home Economics, University of the Philippines Diliman 1991., 1991)
The study was conducted in Bogor district, West Java, Indonesia. The study attempted to determine the significance of mother's age at marriage on pregnancy outcome as well as the nutritional status of both mother and child. The study involves a total of 236 mothers with at least one preschooler child as index child selected through random proportional sampling. The results showed that the average age of mothers 25.3 years and had already experienced 2 to 4 gravidas. They were married and experienced the first pregnancy at relatively young age. Women in the study have just achieved menarch at the time of their first marriage (the mean age at menarch is 13.9 years and the mean age at marriage is 15.7 years) which poses a great health risk for the mother. Marriage at a young age confirms certain adverse effects. The higher the age at marriage, the lower the incidence of failed pregnancy outcome and the better the nutritional status of the mother and their children (i.e. they do not suffer anemia). A negative relationship exists exists between failed pregnancy outcome and the duration of marriage and birth interval. On the other hand, failed pregnancy outcome is positively related with household size and parity. Meanwhile, the child's nutritional status is negatively related with the child's age. Males are also found to have a better nutritional status than the female child. A positive relationship exists between between mother's nutritional status and child's nutritional status when the same measurement (i.e. percentage weight for height)was used in determining the nutritional status of both mother and child. However, a negative relationship was found between mother's nutritional status measured by percentage weight for height and mother's social participation. Although most mothers participated in community programs, a negative relationship was found between mother's social participation and child's nutritional status. There is a perceived difference between successful and unsuccessful mothers. Successful mothers displayed an advantage in terms of socio-demographic factors, nutritional performance, allotted more time for child care, a better attitude towards family and child and social participation.
Computer print-out.
Vita.
Thesis
Keywords: Mothers -- Indonesia -- Nutrition; Children -- Indonesia -- Nutrition; Marriage age -- Indonesia; Mothers -- Indonesia -- Social conditions; Pregnancy -- Indonesia -- Nutritional aspects